Genotype-phenotype correlations for 17 Chinese families with inherited retinal dystrophies due to homozygous variants - Xue Fan; Zhen Li; Lingzhi Sha; Xunlun Sheng; Weining Rong (Scientific Reports)
Abstract In this study, patients with inherited retinal dystrophies (IRDs) who visited Ningxia Eye Hospital from January 2015 to September 2023 were analyzed. Through Whole Exome Sequencing (WES) and Sanger verification, 17 probands carrying homozygous variants were detected. The association between the genotype and clinical phenotype of patients with homozygous variants was analyzed. Among all the patients, 3 patients (17.6%) had a family history of consanguineous marriage, and the onset age of 5 patients(29.4%) was less than 10 years. According to 12 patients (70.6% ), they had the best corrected visual acuity (monocular) < 0.3. 3 were blind, 9 with moderate to severe visual impairment, and 2 with mild visual impairment. 16 homozygous variants were detected in 9 different genes, of which 7 were novel homozygous variants, including frameshift variants, missense variants, and a copy number variant. These variants are related to clinical phenotypes such as Usher syndrome type II (USH2), Stargardt disease (STGD), retinitis pigmentosa (RP), Leber congenital amaurosis (LCA), and Bardet-Biedl syndrome (BBS) respectively. The results of the study indicate that more than 80% of persons with homozygous variant originated from non-consanguineous families, emphasizing the significance of genetic screening for individuals who lack a family history of consanguineous marriage and no obvious clinical phenotypes, but who may carry genetic pathogenic variants for genetic diseases. Furthermore, by analyzing the genotypes and clinical phenotypes of IRD patients from these 17 Chinese families, we have expanded the spectrum of variants in known pathogenic genes for IRDs and the range of clinical phenotypes associated with variants in these genes. We have identified couples at high risk of having affected offspring and individuals with moderate to severe IRDs, providing a basis for genetic counseling, reproductive decision-making, disease prevention, and management. Our findings highlight the association between homozygous variants and more severe clinical phenotypes within these families, thus laying the groundwork for future genetic screening and intervention strategies.